2022
DOI: 10.1186/s12891-022-05677-z
|View full text |Cite
|
Sign up to set email alerts
|

Management of arthrofibrosis in neuromuscular disorders: a review

Abstract: Arthrofibrosis, or rigid contracture of major articular joints, is a significant morbidity of many neurodegenerative disorders. The pathogenesis depends on the mechanism and severity of the precipitating neuromuscular disorder. Most neuromuscular disorders, whether spastic or hypotonic, culminate in decreased joint range of motion. Limited range of motion precipitates a cascade of pathophysiological changes in the muscle-tendon unit, the joint capsule, and the articular cartilage. Resulting joint contractures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 130 publications
2
4
0
Order By: Relevance
“…In our study, we first examined the effect of PLLA on collagen synthesis, and the PIP EIA assay confirmed that procollagen synthesis in dermal fibroblasts gradually increased with increasing PLLA concentration. It is known that type I collagen is the most common type of collagen in the human body, consisting of a type I collagen α 1 chain and a type I collagen α 2 chains, encoded by the COL1A1 and COL1A2 genes 22 . Here, we confirmed that the mRNA levels of COL1A1 and COL1A2 gradually increased with increasing PLLA concentration.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, we first examined the effect of PLLA on collagen synthesis, and the PIP EIA assay confirmed that procollagen synthesis in dermal fibroblasts gradually increased with increasing PLLA concentration. It is known that type I collagen is the most common type of collagen in the human body, consisting of a type I collagen α 1 chain and a type I collagen α 2 chains, encoded by the COL1A1 and COL1A2 genes 22 . Here, we confirmed that the mRNA levels of COL1A1 and COL1A2 gradually increased with increasing PLLA concentration.…”
Section: Discussionsupporting
confidence: 82%
“…It is known that type I collagen is the most common type of collagen in the human body, consisting of a type I collagen α 1 chain and a type I collagen α 2 chains, encoded by the COL1A1 and COL1A2 genes. 22 Here, we confirmed that the mRNA levels of COL1A1 and COL1A2 gradually increased with increasing PLLA concentration. The protein level of COL1A1 also increased gradually.…”
Section: Discussionsupporting
confidence: 76%
“…Collagen, a major protein in the ECM produced by fibroblasts, has a crucial role in providing structural support, strength and elasticity to tissues (4). Among the different types of collagens, type I collagen is the most abundant in the human body and is composed of the Col1A1 and Col1A2 proteins (30). A previous study indicated that Col1A1 is predominantly expressed in fibroblasts, with a higher production ratio compared to Col1A2 (ratio, 2:1) (31).…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue releases have shown promising outcomes in terms of improving knee extension and reducing flexion contracture. However, excessive release can lead to instability or weakening of the soft tissues, requiring careful consideration and surgical planning [16] .…”
Section: Surgical Techniques For Correcting Ffdmentioning
confidence: 99%